2019
DOI: 10.1177/1460458219876188
|View full text |Cite
|
Sign up to set email alerts
|

User involvement in the development of a telehealth solution to improve the kidney transplantation process: A participatory design study

Abstract: Kidney transplantation is the treatment of choice for patients with end-stage renal disease, and leads to everyday self-management of this chronic condition. This article aims to provide documentation for a participatory design study of a telehealth solution to improve the kidney transplantation process, and to identify the impact from the different participants in the participatory design study. Through a participatory design approach, a smartphone application (app) was developed for the entire kidney transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…Patients and HCPs collaborated in developing a solution, guided by the needs of the users in clinical practice (Nielsen, Agerskov, Bistrup, & Clemensen, 2019a, 2019bNielsen, Clemensen, Bistrup, & Agerskov, 2019). The telehealth solution took the form of a new workflow for follow-up consultations and an app for kidney transplant patients as listed in Table 1.…”
Section: The Telehealth Solutionmentioning
confidence: 99%
“…Patients and HCPs collaborated in developing a solution, guided by the needs of the users in clinical practice (Nielsen, Agerskov, Bistrup, & Clemensen, 2019a, 2019bNielsen, Clemensen, Bistrup, & Agerskov, 2019). The telehealth solution took the form of a new workflow for follow-up consultations and an app for kidney transplant patients as listed in Table 1.…”
Section: The Telehealth Solutionmentioning
confidence: 99%
“…Looking into previous research, intervention examples could be telehealth solutions, discharge follow-up or cross-sectoral collaboration. 48 Finally, a 'laboratory' workshop pretesting the prototype sees its feasibility and acceptability in practice. 30 This workshop will include a smaller number of participants as the aim is narrow, compared with the creative, innovative workshops.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic evaluation found that only 23/378 health apps (6%; n = 5 both Android and iOS, n = 12 only Android, n = 11 only iOS) were address the needs of patients with kidney diseases and were able to support because of useful features [36]. Therefore, medical experts or patients themselves should be integrated into the developing process of an app from the beginning to adapt to specific needs [40,41]. Today, start‐up companies and publicly funded projects from medical experts develop flexible eHealth tools tailored to the requirements of patient groups and healthcare providers [31,32,35,41–50].…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%
“…Today, start‐up companies and publicly funded projects from medical experts develop flexible eHealth tools tailored to the requirements of patient groups and healthcare providers [31,32,35,41–50]. Ideally, apps are connectable to the hospital's EHR [41,44], as standalone software limits accessibility and data transfer. Many healthcare IT solutions are outdated for today's requirements lacking interoperability, flexibility, and are not designed for healthcare professionals.…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%